PROSES PENGEBORAN LUBANG BUCKET EXCAVATOR MENGGUNAKAN MESIN LINE BORING DI PD. XYZ - Hasibuan, Zulfahmi Matumona; Nuramal, Agus; Hestiawan, Hendri (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2021)
PD. XYZ that is located in Soeprapto Dalam, Bumi Ayu, Selebar District,  Bengkulu is engaged in the metal working, construction and workshop. To facilitate the process, a machine is needed to help speed up each process. Tools  machine are used to make human work easy. Drilling process is one of the machining process that the aim is to enlarge the diameter of the excavator bucket hole. The purpose of this study are determine drilling process of a bucket excavator and observe the result of drilling on a line drilling machine. The research used a drilling line TPX6113 type that the chisel is YG6. Drilling process is carried out with three feeding process, namely 4mm, 2mm and 2 mm that the feeding speeds are 20 rpm and 31.5 rpm. The result is the smoothest process drilling in the high speed